2022
DOI: 10.1101/2022.01.06.475284
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distinct responses to rare codons in select Drosophila tissues

Abstract: Codon usage bias has long been appreciated to influence protein production. Yet, relatively few studies have analyzed the impacts of codon usage on tissue-specific mRNA and protein expression. Here, we use codon-modified reporters to perform an organism-wide screen in Drosophila melanogaster for distinct tissue responses to codon usage bias. These reporters reveal a cliff-like decline of protein expression near the limit of rare codon usage in endogenously expressed Drosophila genes. Near the edge of this limi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 69 publications
(95 reference statements)
1
0
0
Order By: Relevance
“…Moreover, we also report that some tissues have a more definite codon profile than others, where this second axis is less evident. In agreement with our observed tissue-specific axis, Allen et al (2022) recently reported that testis and brain (in contrast to other tissues such as ovary) better tolerate the translation of rare A/T-ending codons in Drosophila melanogaster 28 .…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, we also report that some tissues have a more definite codon profile than others, where this second axis is less evident. In agreement with our observed tissue-specific axis, Allen et al (2022) recently reported that testis and brain (in contrast to other tissues such as ovary) better tolerate the translation of rare A/T-ending codons in Drosophila melanogaster 28 .…”
Section: Discussionsupporting
confidence: 93%